Amyloid-β peptide dimers undergo a random coil to β-sheet transition in the aqueous phase but not at the neuronal membrane - Fatafta, Hebah; Khaled, Mohammed; Owen, Michael C; Sayyed-Ahmad, Abdallah; Strodel, Birgit (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Mounting evidence suggests that the neuronal cell membrane is the main site of oligomer-mediated neuronal toxicity of amyloid-β peptides in Alzheimer's disease. To gain a detailed understanding of the mutual interference of amyloid-β oligomers and the neuronal membrane, we carried out microseconds of all-atom molecular dynamics (MD) simulations on the dimerization of amyloid-β (Aβ)42 in the aqueous phase and in the presence of a lipid bilayer mimicking the in vivo composition of neuronal membranes. The dimerization in solution is characterized by a random coil to β-sheet transition that seems on pathway to amyloid aggregation, while the interactions with the neuronal membrane decrease the order of the Aβ42 dimer by attenuating its propensity to form a β-sheet structure. The main lipid interaction partners of Aβ42 are the surface-exposed sugar groups of the gangliosides GM1. As the neurotoxic activity of amyloid oligomers increases with oligomer order, these results suggest that GM1 is neuroprotective against Aβ-mediated toxicity.
Keywords: amyloid-β; buněčná membrána; Lipid Bilayers; Protein Multimerization; neuronal membrane; Humans; konformace proteinů; Protein Binding; Protein Conformation; lidé; Alzheimer’s disease; neurony; amyloidní beta-protein; amyloid; molecular dynamics; simulace molekulární dynamiky; Amyloid; lipidové dvojvrstvy; transition network; G(M1) Ganglioside; Amyloid beta-Peptides; Molecular Dynamics Simulation; Neurons; vazba proteinů; G(M1) gangliosid; Cell Membrane; multimerizace proteinu